Methodology for reliability assessment of steel wire ropes under fretting fatigue conditions - Salleh, S. (Universiti Malaysia Pahang, 2017)
This paper describes a newly-developed damage-based fatigue life model for the long-Term reliability assessment of drawn steel wires and wire ropes. The methodology is based on the computed local stress field in the critical trellis contact zone of a stranded wire rope by FE simulations and the estimated fretting damage of the drawn wire material. A case study using a single strand (1x7) steel wire rope with 5.43 mm-dia. drawn wires is employed to demonstrate the damage-based fatigue life prediction procedures. Under applied tensile loading with peak stress corresponding to 50%MBL (ΔP = 145 kN, R = 0.1), the von Mises stress cycles in-phase and with an identical stress ratio to the applied axial load. The damage initiation life at the trellis contact along the core wire is No = 673 cycles with an additional 589 load cycles to reach the first separation of the material point. The threshold load cycle for the fretting fatigue damage is predicted to be 12.3%MBL. An improved data set of the damage model parameters of the drawn steel wires is indispensable in achieving an accurate and validated life prediction model.